Forced Air Design using Thermal Analysis and CFD Simulations of a Brushless DC Motor for the STC-4 Solar Car - Huankhoksung, Witoon; Yabsungnoen, Thamarat (Srinakharinwirot University Engineering Journal, 2025)
This research studies the effect of an air-forced impeller design for cooling brushless direct current (BLDC) electric motors using thermal analysis and computational fluid dynamics (CFD) simulation. The simulation results show that installing an air-forced impeller reduces the temperature of various motor components. Specifically, the temperature of the copper coils is reduced by approximately 59%, the shaft core by approximately 47%, and the air inside the motor by approximately 63%, resulting in better cooling and reducing the risk of damage from overheating. Furthermore, the air temperature between the stator teeth and rotor magnets, as well as the front and rear motor covers, is reduced by approximately 17%, which helps maintain efficiency and extend the motor's lifespan, especially under overload conditions. The results of this research provide guidelines for developing BLDC motor cooling systems to improve their efficiency and broaden their applications.